Alternative Designs for Semarang-Demak Coastal Dike and Toll Road - Andojo Wurjanto; Julfikhsan Ahmad Mukhti; Shinta Ayuningtyas (Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
Semarang city has been experiencing coastal flooding as a major problem. The flooding is inevitable due to the declining groundwater level as an impact of population growth and groundwater exploitation. The Indonesian Ministry of Public Works and Housing is currently planning to build the Semarang-Demak section of the Northern Java Coastal Tollway not only to fulfill traffic demand but also to fight coastal flooding. The purpose of this paper is to present alternative designs to support the plan and to provide recommendations based on design analyses as well as concerns from past design experiences. To the degree that is allowed by the available secondary data, reasonably detailed engineering calculations were performed to be able to present the dimensions of each alternative structure. The results of the structural and geotechnical analyses were obtained using suitable software for each type of analysis and the concerns based on past design experiences were investigated to find the most effective and efficient alternative.